2019
DOI: 10.1093/rheumatology/kez525
|View full text |Cite
|
Sign up to set email alerts
|

Anti-MDA5 juvenile idiopathic inflammatory myopathy: a specific subgroup defined by differentially enhanced interferon-α signalling

Abstract: Objectives JDM and juvenile overlap myositis represent heterogeneous subtypes of juvenile idiopathic inflammatory myopathy (JIIM). Chronic evolution can occur in up to 60% of cases, and morbidity/mortality is substantial. We aimed to describe the clinical, biological, histological and type I IFN status in JIIM associated with anti-melanoma differentiation-associated protein 5 (anti-MDA5) autoantibodies at presentation (group 1) in comparison with other JIIM (group 2). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 58 publications
2
20
0
1
Order By: Relevance
“…A recent French multicenter study identified 13 patients with Juvenile myositis and positive anti-MDA5 antibodies, and this group was constituted equally by Juvenile Dermatomyositis (JDM) and Juvenile Overlap Myositis. They confirmed the presence of ulcerative skin disease and arthritis in frequencies similar to those previously reported; in addition, they identified that a lupuslike rash was present in half of the subjects, and aseptic abscesses in 20% [40].…”
Section: Clinical Phenotype In Children With Anti-mda5 Dmsupporting
confidence: 86%
See 3 more Smart Citations
“…A recent French multicenter study identified 13 patients with Juvenile myositis and positive anti-MDA5 antibodies, and this group was constituted equally by Juvenile Dermatomyositis (JDM) and Juvenile Overlap Myositis. They confirmed the presence of ulcerative skin disease and arthritis in frequencies similar to those previously reported; in addition, they identified that a lupuslike rash was present in half of the subjects, and aseptic abscesses in 20% [40].…”
Section: Clinical Phenotype In Children With Anti-mda5 Dmsupporting
confidence: 86%
“…The cytokine profile in patients with anti-MDA5 DM further supports an upregulated interferon axis (IFN-γ, IFN-α, and IFN-induced protein, IP-10) alongside other proinflammatory cytokines [39,40]. A hierarchical cluster analysis of the cytokine profiles in DM revealed two distinct clusters, with predominance of IFN-related cytokines in cluster one, 75% of which was constituted by anti-MDA5 DM and strong correlation with cutaneous vasculitis [39].…”
Section: Environmentalmentioning
confidence: 66%
See 2 more Smart Citations
“…Melanoma differentiation–associated gene 5 (MDA‐5) is associated with dermatomyositis and often presents with a distinct cutaneous presentation and progressive interstitial lung disease (ILD) (1–3). MDA‐5 signaling often leads to increased interferon signaling, which contributes to atypical vasculopathy, leading to atypical, and at times ulcerative or necrotic, cutaneous manifestations, which are challenging to diagnose and treat (2).…”
mentioning
confidence: 99%